Long-range atmospheric transport and the distribution of polycyclic aromatic hydrocarbons in Changbai Mountain. (January 2015) - Zhao, Xiangai; Kim, Seung-Kyu; Zhu, Weihong; Kannan, Narayanan; Li, Donghao
Highlights: Different distributions of PAHs were observed with elevation and side of mountain. Long-range transport is a major contributor to PAHs in the Changbai Mountain soil. Cold trapping seems to occur on the southern and western sides of the mountain. Local sources in the mountain are minor contributors to PAHs in the mountain soil. Abstract: The Changbai (also known as "Baekdu") Mountain, on the border between China and North Korea, is the highest mountain (2750 m) in northeastern China. Recently, this mountain region has experienced a dramatic increase in air pollution, not only because of increasing volumes of tourism-derived traffic but also because of the long-range transport of polluted westerly winds passing through major industrial and urban cities in the eastern region of China. To assess the relative importance of the two sources of pollution, 16 polycyclic aromatic hydrocarbons (PAHs) as model substances were determined in the mountain soil. A total of 32 soil samples were collected from different sides of the mountain at different latitudes between July and August of 2009. The ∑PAH concentrations were within the range 38.5–190.1 ng g −1 on the northern side, 117.7–443.6 ng g −1 on the southern side, and 75.3–437.3 ng g −1 on the western side. A progressive increase in the level of ∑PAHs with latitude was observed on the southern and western sides that face the westerly wind with abundant precipitation. However, a similar concentration gradient was not observed on the northern side that receives less rain and is on the leeward direction of the wind. The high-molecular-weight PAH compounds were predominant in the soils on the southern and western sides, while low-molecular-weight PAHs dominated the northern side soils. These findings show that the distribution of PAHs in the mountain soil is strongly influenced by the atmospheric long-range transport and cold trapping.